Democratic Leadership Style of Public and Private Elementary School Principals During The Covid-19 - Riski, Samsu; Hamami, Tasman; Yamin, M Nurul (JURNAL AL-TANZIM, 2022)
This research aims to analyze and understand the democratic leadership style of the head of Ngrukumen public elementary school and Muhammadiyah Girikerto Yogyakarta Private during the Covid-19 pandemic. This research uses a descriptive qualitative approach. Data collection techniques in this study use observation, interviews, and documentation. This study's data analysis techniques use data analysis, data presentation, and drawing conclusions or verification. The analysis and research data results showed that the democratic leadership style of the head of Ngrukumen State Elementary School during the Covid-19 pandemic used a systematic democratic leadership style. The democratic leadership style of the head of Muhammadiyah private elementary school Girikerto Yogyakarta during the pandemic uses a combined democratic combination leadership style between democratic, transactional, and charismatic.